Correction: Isolated Fe and Co dual active sites on nitrogen-doped carbon for a highly efficient oxygen reduction reaction. Issue 38 (26th April 2018) - Zhang, Diyang; Chen, Wenxing; Li, Zhi; Chen, Yuanjun; Zheng, Lirong; Gong, Yue; Li, Qiheng; Shen, Rongan; Han, Yunhu; Cheong, Weng-Chon; Gu, Lin; Li, Yadong
Abstract : Correction for 'Isolated Fe and Co dual active sites on nitrogen-doped carbon for a highly efficient oxygen reduction reaction' by Diyang Zhang et al., Chem. Commun., 2018, DOI: ;10.1039/c8cc00988k .